2017
DOI: 10.1097/md.0000000000008259
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of retroperitoneal laparoscopic deroofing of simple renal cyst with perirenal fat tissue wadding technique

Abstract: Treatment options for simple renal cyst (SRC) include open surgery, laparoscopy with decortication, or percutaneous aspiration with or without sclerotherapy. Though laparoscopic unroofing achieves better results than percutaneous sclerotherapy, the reported recurrence rate is still up to 19%. Thus, it is necessary to find methods to reduce the recurrence rate.To investigate whether the perirenal pedicled fat tissue wadding technique during retroperitoneal laproscopic deroofing (RLD) of SRC affects the incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
1
4
1
Order By: Relevance
“…Most of the cysts were located in the left kidney (39.4%), followed by right kidney (30.3%) and bilateral kidney (30.3%), with χ 2 = 0.545, p = 0.761; thus, the results were not considered statistically significant. These results were similar to other reports, such as those published studies by Nguyen Ngoc Anh (52.78%) 6 , Dinh Le Quy Van (42.1%) 7 , and Shicong Lai (55,1%) 9 . Most of the cysts were located in the lower pole (54.6%), followed by upper pole (42.4%) and peripelvic (3%), with χ 2 = 14.364, p = 0.001.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Most of the cysts were located in the left kidney (39.4%), followed by right kidney (30.3%) and bilateral kidney (30.3%), with χ 2 = 0.545, p = 0.761; thus, the results were not considered statistically significant. These results were similar to other reports, such as those published studies by Nguyen Ngoc Anh (52.78%) 6 , Dinh Le Quy Van (42.1%) 7 , and Shicong Lai (55,1%) 9 . Most of the cysts were located in the lower pole (54.6%), followed by upper pole (42.4%) and peripelvic (3%), with χ 2 = 14.364, p = 0.001.…”
Section: Discussionsupporting
confidence: 92%
“…Simple aspiration or sclerotherapy is a minimally invasive procedure; however, the recurrence rate is very high. Open surgery offers a high success rate; however, it presents an invasive procedure with the comorbidity of flank incision 4,5 . The laparoscopic technique, however, not only has a high success rate but is also characterized by minimal invasiveness, low morbidity, and early recuperation, making it a preferred treatment 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the efficiency of LD treatment, Lai and colleagues [29] studied the impacts of perirenal pedicled fat tissue wadding technique (PPFTWT) on the recurrence rate during this surgery operation, they found that LD using PPFTWT can decrease the rate of cyst recurrence evidently. Inserting fat tissue into the cavity of the cyst and fixing it prevented the cyst wall from adhering to the residuary cyst wall or surrounding tissue, and contributed to the secretion drainage and absorption of the remaining cyst wall, thus declined the risk of cyst recurrence [30].…”
Section: Discussionmentioning
confidence: 99%
“…[27] Hence, LD could be the standard in the management of renal cysts, especially suited for patients failed after AS therapy. [28] To enhance the efficiency of LD treatment, Lai and colleagues [29] studied the impacts of perirenal pedicled fat tissue wadding technique (PPFTWT) on the recurrence rate during this surgery operation, they found that LD using PPFTWT can decrease the rate of cyst recurrence evidently. Inserting fat tissue into the cavity of the cyst and fixing it prevented the cyst wall from adhering to the residuary cyst wall or surrounding tissue, and contributed to the secretion drainage and absorption of the remaining cyst wall, thus declined the risk of cyst recurrence.…”
Section: Discussionmentioning
confidence: 99%